Is AD a Stress-Related Disorder? Focus on the HPA Axis and Its Promising Therapeutic Targets - Canet, Geoffrey; Hernandez, Célia; Zussy, Charleine; Chevallier, Nathalie; Desrumaux, Catherine; Givalois, Laurent (Frontiers in Aging Neuroscience, 2019)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder that has important health and economic impacts in the elderly. Despite a better understanding of the molecular mechanisms leading to the appearance of major pathological hallmarks (senile plaques and neurofibrillary tangles), effective treatments are still lacking. Sporadic AD forms (98% of all cases) are multifactorial, and a panoply of risk factors have been identified. While the major risk factor is aging, growing evidence suggests that chronic stress or stress-related disorders increase the probability to develop AD. An early dysregulation of the hypothalamic-pituitary-adrenal axis (HPA axis or stress axis) has been observed in patients. The direct consequence of such perturbation is an oversecretion of glucocorticoids (GC) associated with an impairment of its receptors (glucocorticoid receptors, GR). These steroids hormones easily penetrate the brain and act in synergy with excitatory amino acids. An overexposure could be highly toxic in limbic structures (prefrontal cortex and hippocampus) and contribute in the cognitive decline occurring in AD. GC and GR dysregulations seem to be involved in lots of functions disturbed in AD and a vicious cycle appears, where AD induces HPA axis dysregulation, which in turn potentiates the pathology. This review article presents some preclinical and clinical studies focusing on the HPA axis hormones and their receptors to fight AD. Due to its primordial role in the maintenance of homeostasis, the HPA axis appears as a key-actor in the etiology of AD and a prime target to tackle AD by offering multiple angles of action.